Organizational Diversity Perception in Muhammadiyah - Yuwono, Susatyo; Himam, Fathul; I.J.K. , Sito Meiyanto; Anief , Sofyan (International Journal of Psychosocial Rehabilitation, 2020)
Purpose: This study aims to describe the conditions of organizational diversity in AUM of Solo city under the management of Regional Executive of Muhammadiyah of Solo (Pimpinan Daerah Muhammadiyah/PDM Solo) and the perceptions of the Muhammadiyah leaders about this condition. Methodology: The subjects of this qualitative research were four managers of AUM and two heads of assemblies in PDM of Solo city.The data were collected by interviews and documentation of demographic data.. Results: the uniqueness found in the organizationaldiversity reflects the potentials of each organization of AUM. These potentials were seen as an opportunity to take advantage of the diversity in achieving the objectives, vision and mission of the Muhammadiyah organization. This leads to a perception that organizational diversity is a grace (berkah) and blessing (rahmat) for AUMApplications/Originality/Value: This research is studying lower level of organizational diversity management in a religious organization, in particular the Muhammadiyah. Further research is needed to explore the dynamics of organizational diversity and its management method to reach excellences.